Assessing Climate Change Impacts: Agriculture - Francesco Bosello; Jian Zhang (Fondazione Eni Enrico Mattei (FEEM), 2005)
The economy-wide implications of climate change on agricultural sectors in 2050 are estimated using a static computable general equilibrium model. Peculiar to this exercise is the coupling of the economic model with a climatic model forecasting temperature increase in the relevant year and with a crop-growth model estimating climate change impact on cereal productivity. The main results of the study point out on the one hand the limited influence of climate change on world food supply and welfare; on the other hand its important distributional consequences as the stronger negative effects are concentrated on developing countries. The simulation exercise is introduced by a survey of the relevant literature.
Keywords: D58; C68; N50; Q54; 330; Climate change; Computable general equilibrium models; Agriculture; Klimaveränderung; Landwirtschaft; Produktivität; Allgemeines Gleichgewicht; Welt